Investigation Of Determinants Of Customer Satisfaction - Aprih Santoso; M. Hasan Ma’ruf (Universitas Wahid Hasyim Semarang, 2022)
Abstract The issue with PDAM Tirta Moedal Semarang is that it causes customers to feel unsatisfied, which leads to complaints like: water frequently dies and comes out sparingly. The goal of the study was to determine how trust, an intervening variable, affected the relationship between PDAM Tirta Moedal Semarang's service reputation and customer happiness. The population of this research is the housing community of Graha Mukti Semarang as many as 1,537 people. There were 99.87 samples total in this investigation (based on the Slovin formula, rounded to 100 individuals).The SPSS 26 application was used to carry out the analysis technique. Through path analysis, the variable influence model will be put to the test.The findings demonstrate a direct correlation between service quality and confidence in PDAM Tirta Moedal Semarang. The service quality and reputation of PDAM Tirta Moedal Semarang has an immediate impact on PDAM Tirta Moedal Semarang's client satisfaction. Customer satisfaction at PDAM Tirta Moedal Semarang is directly impacted by trust. At PDAM Tirta Moedal Semarang, trust can be considered an intervening variable on service quality and reputation on customer satisfaction. Keyword : Satisfaction; trust; service; reputation